(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This paper considers the kinematics of a six-link impact mechanism with the largest crank, with improved kinematic and dynamic parameters, synthesised on the basis of a crank and two-crank articulated four-link mechanism with special link positions. This mechanism was developed by the authors of the article and the Eurasian patent for invention was obtained in 2022. In the article, based on the results of kinematic analysis of the six-link percussion mechanism with the largest yoke, the feasibility of its use as an actuating mechanism in the creation of new percussion and percussion-rotating machines used in the mining industry, as well as in construction and road-building works is substantiated.